Interpersonal Relationship to Tackle At-Risk Students: A Case Study in EFL Learning - Katharina Rustipa (Celt: A Journal of Culture, English Language Teaching & Literature, 2018)
This study investigated interpersonal relationship to tackle at-risk students’ low competence, inactive class participation, misbehave. This research especially aims at knowing how positive, supportive teacher-at risk student relationship can enhance the student’s learning outcome, how teacher-student relationship can enhance students’ motivation, can activate the at-risk students. This study is descriptive in nature held in a classroom context in sentence writing class in Stikubank University (UNISBANK) Semarang, Indonesia. The results of the study revealed how the at-risk student’s perception on teacher’s affective qualities can affect their learning outcome. It is concluded that the more positive the at-risk student’s perception on the teacher-student relationship, the higher the learning outcome she/ he achieves. The positive at-risk students’ perception on their teacher’s affective qualities makes them achieve the learning outcome successfully. This is because they feel that their teacher creates a safe and trustful environment that makes them feel free to share difficulties. Thus, supportive and caring teacher-at risk student relationship is essential in teaching-learning process.